Chronic Chagas cardiomyopathy - Vera Demarchi Aiello; Fernando Peixoto Ferraz de Campos (University of São Paulo, 2015)
First described by Carlos Justiniano Ribeiro Chagas (1879-1934) in 1909, Chagas disease (CD) or American trypanosomiasis is caused by the protozoan parasite Trypanosoma cruzi. This zoonotic infectious disease follows a sylvatic cycle where blood-sucking triatomine insect (known as kissing bug or in Portuguese as "barbeiro"), acquire the parasite by sucking small mammals' blood and transmit to humans through their feces, left close to the bite site. The parasite, in turn, reaches the human blood stream when the parasite‑laden feces are dispersed at the itching bite wound.